(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
In the globalized world, foresight is characterized by a holistic process that allows construction in future scenarios, establishing from the application of capital consolidation slogans as equitable growth, economic development and social networks collaborative work social community centered on the individual, therefore, the theoretical and practical use of foresight and social capital are reflected in public policies of states. This article aims to present a prospective plan for the city of Pamplona determining lines of action to display the city’s long-term and major players that integrate capital network. The theoretical foundation is based on the contents of Medina and Ortegón (2007), Miklos (2000), Fukuyama (2001) among others, carried by an interpretive approach, through a qualitative methodology, descriptive, using documentary analysis, die design appropriate to the context under study and prospective models. Also being supported in previous studies as the three economic development forums developed from 2008 to 2010, which formed the basis for the prospective as background process. It is noteworthy that studying in Pamplona Norte de Santander factors such as trade, services, industry, tourism, agriculture, supportive and educational likely envision a future in front of a desirable future by reasoning about the impact that social capital fosters development strategy.